ANALYSIS OF CLASS X STUDENTS' COMPETENCY IN MEMORIZING THE AL-QUR'AN AT MADRASAH ALIYAH NEGERI 1 MEDAN - Syahdan, Syahdan; Nuraisyah, Nuraisyah; Afilah, Afifah; Rangkuti, Charles (Proceeding International Seminar of Islamic Studies, 2024)
Memorizing the Qur'an is an activity that has the qualities of high honor before Allah SWT, even before other humans. In the current era, many educational institutions are focusing their attention on improving Al-Quran tahfidz activities. One educational institution that focuses on memorizing the Koran is Madrasah Aliyah Negeri 1 in the city of Medan. At MAN 1 Medan, as an Islamic educational institution that has a vision and mission to produce a generation that memorizes the Al-Quran, increasing the competency of memorizing the Al-Quran in class X students is a very relevant thing to research. because at this stage students begin to take a higher and more complex curriculum. This research uses a qualitative method where data collection techniques are carried out using observation, interviews and documentation. The results of this research show that the competencies possessed by some students in memorizing the Al-Qur'an at MAN 1 Medan have ideal competencies. The first factor inhibiting students' memorization is the lack of repetition due to the large number of activities carried out so that students feel tired. Second, they cannot read the Al-Qur'an properly and correctly. Third, they are not consistent in memorizing. while the supporting factors are, firstly, support from parents and family, secondly support from the school, thirdly, motivation within the students themselves.